Bringing Zull’s Four Brain-derived Pillars of Learning into the English Classroom - Jorge Carlos Correa Rodriguez (Universitas Ahmad Dahlan, 2020)
Teaching modifies the brain of the learners. In that respect, providing teachers with information about ways in which the brain learns could allow them to enhance their practices. Similarly, language teachers should also embrace what experts and theories from Educational Neuroscience and Mind, Brain and Education Science (MBE) Science can offer to pedagogy. This paper explored Zull’s biological learning model in order to provide a practical way to support language teaching. The model depicts 4 pillars derived from his understanding of the learning brain. Zull’s model was developed by his observations of the organic structure of the brain. It originated from the functioning of specific areas located in the neocortex of the brain; the sensory area, the back-integrative area, the front-integrative area and the motor area. Zull (2002) posited that each area is in charge of general functions such as; gathering, reflecting, creating and testing respectively. This connection could benefit the teaching process by providing a path to follow at the moment of instruction. In that sense, this paper observed how his model could be connected with one language teaching methodology. Presentation, practice and production (PPP). It was also observed that the synergetic nature of the connections within the human brain allows the pillars to move throughout the stages of PPP. It means that despite each stage was bound to specific pillars, the rest of them could be also used in each particular stage of PPP if needed. Moreover, some suggestions for the general language classroom were also included. This paper, therefore, aimed to connect one theory derived from the understanding of the brain with pedagogy in order to enhance the way teaching and learning in language classrooms is conducted.